Economic evaluations of interventions for the prevention and treatment of pressure ulcers: an umbrella review protocol. Issue 2 (5th February 2022) - Klugarová, Jitka; Pokorná, Andrea; Hussain, Salman; Vrbová, Tereza; Slezáková, Simona; Búřilová, Petra; Saibertová, Simona; Dolanová, Dana; Klugar, Miloslav
ABSTRACT: Objective: The objective of this review is to synthesize the findings of economic evaluations of preventing or treating pressure ulcers. Introduction: Pressure ulcers are one of the most common preventable complications characterized by local tissue injury. Pressure ulcers increase mortality rates, impair quality of life, increase the length of hospital stay, and alter overall health outcomes. Published studies have found higher costs associated with treating pressure ulcers than preventing them, with treatment cost varying based on the pressure ulcer category (the greater the category, the higher the cost). We will systematically review the evidence on preventing or treating pressure ulcers from an economic perspective. Inclusion criteria: We will include systematic reviews that investigate both the cost and outcomes associated with the prevention or treatment of pressure ulcers. Systematic reviews dealing with economic evaluation of wound care or management will be excluded if they have not provided separate information for pressure ulcers. Methods: Epistemonikos, MEDLINE, NHS Economic Evaluation Database, and the Canadian Agency for Drugs and Technologies in Health (CADTH) website will be searched for relevant systematic reviews from inception and without any language restrictions. Titles and abstracts will be screened at the initial stage, followed by full-text screening. Quality assessment will be done using the standard JBI critical appraisal instrument for systematic reviews and research syntheses. Article screening, data extraction, and quality assessment will be performed by two reviewers independently. All economic health outcomes will be considered under the primary outcomes of the study. Systematic review registration number: Open Science Framework (https://osf.io/9y2a7/ ).